Hubungan Dukungan Suami dan Paritas dengan Hiperemesis Gravidarum pada Ibu Hamil Trimester I dan II - Gunawan, Ayu Amelya (Universitas Ivet, 2024)
According to the World Health Organization (WHO), pregnancies with hyperemesis gravidarum reach 12.5% of all pregnancies in the world. The aim of the research was to determine the relationship between husband's support and parity with hyperemesis gravidarum in pregnant women in the first and second trimesters of PMB Miftahul Jannah. This research is a quantitative research with a cross sectional research design. The population in this study was 539 pregnant women in the first and second trimesters at PMB Miftahul Jannah. The sampling technique used accidental sampling as many as 54 people. Data analysis uses univariate and bivariate analysis with statistical tests using the chi-square test. The results of the research that has been carried out are obtained from the results of data analysis using the chi-square Test, showing that husband's support is related to hyperemesis gravidarum (p=0.005), parity (p=0.028) with hyperemesis gravidarum in pregnant women in the first and second trimesters. The conclusion of this research is that there is a relationship between husband's support and parity and hyperemesis gravidarum. It is recommended that it can be used as material to add insight and new knowledge in the field of research, especially in cases of pregnancy against hyperemesis gravidarum.